Assessment of critical mathematical thinking skills: A literature review - Evendi, Erpin; Retnawati, Heri; Istiyono, Edi (Beta: Jurnal Tadris Matematika, 2023)
[English]: This study aims to review several previous studies concerning the assessment of critical thinking skills in mathematics learning. This study used the method known as Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), consisting of four stages: identification, screening, eligibility, and inclusion. SCOPUS database was used as the main source in the document selection since it is considered one of the most accurate international indexing systems. The detailed document selection was carried out in the following order: (1) the identification was performed by restricting the SCOPUS database search on the context of critical thinking assessment in mathematics learning and resulted in 147 documents; (2) the first screening based on a restriction of year range (the last 10 years: from 2013 to 2023) resulted in 121 documents and the second screening based on the types of documents (journal articles and conference papers) resulted in 102 documents; (3) in the eligibility stage, 19 documents were found to be relevant to the subject area of mathematics learning; and (4) in the inclusion stage, 11 documents were selected manually based on the keywords and citation and used as the review materials in this study. The existing studies reveal the importance of critical thinking in mathematics learning and present various approaches and instruments that can be adopted to assess the critical thinking skills in the context of mathematics learning. However, the facts about the peculiarities of critical thinking are still unresolved due to the abundance of theories according to different perspectives, thus causing the emergence of various measurement standards on critical thinking skills in mathematics learning. Therefore, the definition of critical thinking in a more specific context, such as mathematics learning, needs to be established, and the instruments used to assess the critical thinking skills in this specific context need to be developed. [Bahasa]: Studi ini bertujuan meninjau sejumlah literatur mengenai asesmen terhadap keterampilan berpikir kritis dalam pembelajaran matematika. Studi ini menggunakan metode Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), yang meliputi empat tahap: identification, screening, eligibility, dan inclusion. Seleksi dokumen mengambil sumber dari database SCOPUS, yang merupakan salah satu sistem pengindeksan internasional paling akurat. Detail seleksi dokumen dilakukan sesuai urutan berikut: (1) identification dengan membatasi pencarian SCOPUS pada konteks penilaian berpikir kritis dalam pembelajaran matematika menghasilkan 147 dokumen; (2) screening pertama berdasarkan pembatasan rentang tahun (10 tahun terakhir: dari 2013 sampai 2023) menghasilkan 121 dokumen dan screening kedua berdasarkan tipe dokumen (journal article dan conference paper) menghasilkan 102 dokumen; (3) pada tahap eligibility, ditemukan 19 dokumen yang relevan dengan topik pembelajaran matematika; dan (4) pada tahap inclusion, ditemukan 11 dokumen yang diseleksi secara manual berdasarkan kata kunci dan artikel yang telah disitasi dan kemudian menjadi materi tinjauan dalam studi ini. Hasil studi ini menunjukkan pentingnya berpikir kritis dalam pembelajaran matematika, serta menyajikan berbagai pendekatan serta instrumen yang dapat digunakan untuk mengasesmen keterampilan berpikir kritis dalam konteks pembelajaran matematika. Namun, fakta tentang kekhasan dalam berpikir kritis masih belum terselesaikan karena banyaknya teori menurut sudut pandang yang berbeda, sehingga membuat standar pengukuran dan penilaian berpikir kritis dalam pembelajaran matematika pun menjadi berbeda-beda. Oleh karena itu, pendefinisian berpikir kritis pada konteks yang lebih spesifik, seperti pembelajaran matematika, perlu dilakukan, dan instrumen yang digunakan untuk mengasesmen keterampilan berpikir kritis dalam pembelajaran matematika perlu dikembangkan.